Bioactivity, Compounds Isolated, Chemical Qualitative, and Quantitative Analysis of Cymbaria daurica Extracts - Gong, Xue; Wang, Jie; Zhang, Meiying; Wang, Peng; Wang, Congcong; Shi, Ruyu; Zang, Erhuan; Zhang, Mingxu; Zhang, Chunhong; Li, Minhui (Frontiers in Pharmacology, 2020)
Cymbaria daurica L. is widely used in traditional Mongolian medicine for the treatment of impetigo, psoriasis, pruritus, fetotoxicity, and diabetes. Therefore, the anti-inflammatory and α-glucosidase-inhibitory activities of four polar C. daurica extracts (water, n-butanol, ethyl acetate, and petroleum ether extract) were preliminarily evaluated to identify the active extracts. We also investigated the chemical composition of the active extracts by phytochemical analysis. The n-butanol and ethyl acetate extracts exhibited significant (p < 0.05) anti-inflammatory activities by inhibiting lipopolysaccharide-induced nitric oxide (NO) production in RAW 264.7 cells. None of the tested extracts exhibited cytotoxic effects at the effective concentrations. The ethyl acetate extract significantly inhibited α-glucosidase activity, and the inhibition potency was equivalent to that of acarbose (p > 0.05). The n-Butanol extract presented the second highest inhibitory activity. As the n-butanol and ethyl acetate extracts were found to have potent anti-inflammatory and α-glucosidase-inhibitory activities, we separated and identified 10 compounds from the extracts. Among them, vanillic acid, cistanoside F, echinacoside, arenarioside, verbascoside, isoacteoside, and tricin were isolated from C. daurica for the first time. Further, 30 compounds from the n-butanol and ethyl acetate extracts of C. daurica were identified using UHPLC-Q-Exactive. The present study demonstrates for the first time that C. daurica contains phenylethanoid glycosides. In addition, this novel HPLC method was subsequently used for simultaneous identification of five compounds in the n-butanol and ethyl acetate extracts of C. daurica. This study provides a chemical basis for further characterization and utilization of C. daurica, which could be a potential source of novel anti-diabetic and anti-inflammatory agents.